The Model Family Code and the regulation of Polish Family Law - Sokołowski, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The paper presents the comparison between the principles of Model Family Code and the regulations Polish family Law. The main questions are connected with the sources of Family Law, the recognition of the clause on “a child’s welfare”, the scope of State’s protection of families and family life and the influence of the European Court of Human Rights’ jurisprudence. In addition, the analyse takes into account the definitions of marriage, concubinage and partnership in connection with the protection of privacy and family life. On the area of divorce regulation the main analyse are connected with the alternative dispute resolution (ADR), parental authority, joint custody and contacts with common child, and financial consequences of dissolution of marriage. At last are analysed the descent of a child, alimentation, adoption the new institution of child’s advocate.